THE ROLE OF COMPUTER TECHNOLOGIES IN TEACHING RUSSIAN AS A NON-NATIVE LANGUAGE (Web of Technology: Multidimensional Research Journal, 2024)
Computer technologies are methods, techniques, methods, means that are used to collect, process, store, operate and transmit information using electronic computing devices and systems, software equipment. The article substantiates that the use of computer technologies in the study of Russian as a non-native language has certain advantages: they improve the educational process, contribute to the development of independence and creativity in building an educational trajectory. Computer technology is a tool that complements traditional teaching methods and serves as auxiliary elements within the lesson. When organizing independent work or independent study of Russian as a foreign language, computer technologies can act as the main ones.